Melatonin pretreatment on exosomes: Heterogeneity, therapeutic effects, and usage - Zhou, Zilan; Wang, Ruiping; Wang, Jie; Hao, Yujia; Xie, Qingpeng; Wang, Lu; Wang, Xing (Frontiers in Immunology, 2022)
The therapeutic outcomes of exosome-based therapies have greatly exceeded initial expectations in many clinically intractable diseases due to the safety, low toxicity, and immunogenicity of exosomes, but the production of the exosomes is a bottleneck for the wide use. To increase the yield of the exosomes, various solutions have been tried, such as hypoxia, extracellular acidic pH, etc. With a limited number of cells or exosomes, an alternative approach has been developed to improve the efficacy of exosomes through cell pretreatment recently. Melatonin is synthesized from tryptophan and secreted in the pineal gland, presenting a protective effect in pathological conditions. As a new pretreatment method, melatonin can effectively enhance the antioxidant, anti-inflammatory, and anti-apoptotic function of exosomes in chronic kidney disease, diabetic wound healing and ischemia-reperfusion treatments. However, the current use of melatonin pretreatment varies widely. Here, we discuss the effects of melatonin pretreatment on the heterogeneity of exosomes based on the role of melatonin, and further speculate the possible mechanisms. Finally, the therapeutic use of exosomes and the usage of melatonin pretreatment are described.